„Karany za pomówienie”. Okoliczności postępowania karnego przeciwko funkcjonariuszowi SB Romualdowi Jankowskiemu przed wojskowym wymiarem sprawiedliwości (1982–1984) - Otta, Mateusz (Aparat Represji w Polsce Ludowej 1944-1989, 2023)
In the article, author is trying to discover the reasons behind this rather untypical, especially for the Polish People’s Republic, judicial verdict. On one hand there was a strong evidence coming from the victim and determination of his representative – lawyer Jerzy Pomina but from the other a probable desire to symbolically authenticate the communist justice system. The only demonstrative nature of the verdict was evidenced not only by the very low sentence, but also the failure to detect the other perpetrators of the crime, disregarding the threat of Heller’s dismissal from work and incarnating him into the army for mock exercises of reservists, as well as the fact that the convicted officer remained in service until 1990.